Detention of children and adolescents under mental health legislation: a scoping review of prevalence, risk factors, and legal frameworks - Lisa Schölin; Zack Tucker; Arun Chopra; Rohan Borschmann; Colin McKay (BMC, 2024)
Abstract Background For individuals with severe mental illness, involuntary assessment and/or treatment (hereafter detention) can be a necessary intervention to support recovery and may even be lifesaving. Despite this, little is known about how often these interventions are used for children and adolescents. Methods This global scoping review set out to: (1) map the current evidence around mental health detentions of children and adolescents (< 18 years); (2) identify the clinical, sociodemographic, and behavioural factors associated with detention; and (3) document the views of professionals and young people on the implementation of mental health legislation. Results After searching databases of peer-reviewed literature and citation chaining, 42 articles from 15 jurisdictions were included. About one fifth of psychiatric admissions in national register data were detentions, however trends were only available for a few high-income Western countries. The circumstances justifying detention and the criteria authorising detention varied between studies, with a mix of clinical factors and observed behaviours reported as the reason(s) warranting/precipitating a detention. Particular groups were more likely to experience detention, such as children and adolescents from minority ethnic communities and those with a documented history of abuse. There was a notable absence of qualitative research exploring the views of professionals or children and adolescents on detention. Conclusion Further research is needed to explore the impact of detention on those aged < 18 years, including national register-based studies and qualitative studies. This is particularly relevant in nations currently undergoing legislative reform.